دور مادة التربية المدنية في اكتساب مفهوم قيم المواطنة لدى تلاميذ المرحلة الأبتدائية من وجهة نظر الأساتذة. -دراسة ميدانية ببعض المدارس الابتدائية بولاية الأغواط - بن مهية خديجة; قرينات بن شهرة (My University, 2023)
This study aimed to reveal the role of teaching civic education in acquiring the values of citizenship among primary school students from the point of view of primary education teachers, in some schools in the state of Laghouat. A tool was used, represented by a questionnaire, which was applied to a sample of (60 ((A male and female professor) from the primary education stage, and the descriptive analytical approach was relied upon. The results showed that there is a role for teaching civic education in acquiring the values of citizenship among primary school students from the teachers’ point of view, based on the axes of the tool in its three dimensions (identity and homeland), (Dialogue and acceptance of others), (cultural and civilizational affiliation). The results also showed that there are differences in the role of teaching civic education in acquiring the values of citizenship among students from the point of view of teachers, attributed to seniority in favor of more than (20) and academic qualification in favor of (graduates of the institute). .Keywords: citizenship values, civic education, primary education teachers